Partial replacement of meat and fat with hydrated wheat fiber in beef burgers decreases caloric value without reducing the feeling of satiety after consumption - Carvalho, Larissa Tatero; Pires, Manoela Alves; Baldin, Juliana Cristina; Sichetti Munekata, Paulo Eduardo; Leandro de Carvalho, Francisco Allan; Rodrigues, Isabela; Polizer, Yana Jorge; Malagoli de Mello, Juliana Lolli [UNESP]; Lapa-Guimaraes, Judite; Trindade, Marco Antonio (Elsevier B.V., 2019)
The aim of this study was to evaluate the effects of different levels of hydrated wheat fiber replacing meat and fat in beef burgers on technological characteristics, sensory acceptance and hunger satisfaction. The different levels of hydrated wheat fiber (1 g fiber: 6 g water) were 0, 1.25, 2.5, 3.75 and 5.0 g of fiber/80 g burger portion. Results showed that the greater the addition of hydrated wheat fiber, the lower the protein (P < .0001) and lipid (P = .0006) content and consequently the greater the reduction in caloric value. Burgers with up to 3.75 g fiber/80 g portion showed the same (P > .05) sensory acceptance as the Control burgers (those without added fiber). Sandwiches comprised of burgers with 2.5 and 5.0 g fiber/80 g portion caused the same (P > .05) hunger satisfaction (satiety feeling) as those comprised of Control burgers for up to 3 h after consumption. Burgers containing 3.75 g fiber/80 g burger may represent an interesting alternative for people who want to reduce caloric intake and/or increase the proportion of insoluble fiber in their diet.
Keywords: Dietary fiber; Hunger satisfaction; Meat product; Caloric value; Affective sensory evaluation